The Influence of Promotion and Distribution Accuracy on Consumer Purchase Interest in PT. Enzym Bioteknologi Internusa - Achmad Rozi (Universitas Negeri Makassar, 2020)
The implementation of promotional activities carried out by the company includes advertising, sales promotion, personal sales, and publicity. This study aims to determine the effect of promotion and accuracy of distribution of consumer buying interest at PT. Enzym Biotechnology Internusa. The method used was explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study have a significant influence on consumer buying interest of 41.1%, hypothesis testing obtained significance 0,000 <0.05. The accuracy of the distribution has a significant effect on consumer buying interest by 39.1%, the hypothesis test obtained a significance of 0,000 <0.05. Promotion and accuracy of distribution simultaneously have a significant effect on consumer buying interest of 50.2%, the hypothesis test obtained significance of 0,000 <0.05.